PENGARUH MODEL PBI TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS X SMA NEGERI KABUPATEN PESISIR SELATAN - Okviani Syafti (STKIP Pesisir Selatan, 2016)
This research began from issues of the low Problem solving skills abilities students of class X SMAN Kabupaten Pesisir Selatan.This research is aimed to reveal the effect of PBI models in problem solving skills students ability started from high, medium and low, as well as the interaction between the model and the learning ability of students in influencing early problem-solving abilities and students mathematical creative thinking. This research is a quasi experimental design of The Randomized Posttest Only Control Group Design. The population in this research is all students of class X SMAN Pesisir Selatan. The sampling technique used is Random Sampling. Samples of this research are the students of class X SMAN 2 Lengayang in the class X.4 as the experimental class and class X.1 as the control class. The instrument used is a test consists of beginning capabilities test and Posttest to see the problem-solving ability. Data analysis was performed using t-test and ANAVA two ways for interaction.There are some conclusions that can be acquired based on the results of research and discussion. First, the students which use PBI have higher problem solving skills than students that use the conventional learning. Second, problem solving high ability students that using PBI model of learning higher than students using the conventional learning.Third, the starting students mathematical problem solving ability is medium and the students which use PBI higher than students using conventional learning. Fourth, the mathematical problem solving ability of low level students that use PBI models less than students using the conventional learning.Fifth, there is no interaction between the model of learning and the prior knowledge of students in influencing the problem solving mathematical.Keywords : Problem Based Instruction(PBI), Problem Solving, Kemampuan Awal.